Dampak Banjir Terhadap Letak Geografis dan Kerentanan Wilayah: Sebuah Kajian Literatur - Jannah, Miftahul; Juandrif, Refi Putri; Hendri, Voni Defri; Ikhwan, Ikhwan (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to examine the relationship between flood impacts, geographical location, and regional vulnerability in Indonesia through a literature study approach. The results of the study show that geographical locations such as lowlands, basins, watersheds, and coastal areas greatly affect the level of regional vulnerability to flooding. In addition to physical factors, social and economic aspects such as population density, poverty level, and land use change due to urbanization also increase the risk and impact of flooding. Floods not only cause physical and economic damage, but can also permanently change the configuration of geographic areas, exacerbating future vulnerability. Consequently, this research emphasizes the importance of a multidimensional approach to flood management, with the integration of physical, social, economic and environmental aspects, supported by Geographic Information System (GIS)-assisted vulnerability mapping, to sustainably reduce disaster risks and impacts.